Moving Bed Gasification of Low Rank Alaska Coal - Mandar Kulkarni; Rajive Ganguli (Journal of Combustion)
This paper presents process simulation of moving bed gasifier using low rank, subbituminous Usibelli coal from Alaska. All the processes occurring in a moving bed gasifier, drying, devolatilization, gasification, and combustion, are included in this model. The model, developed in Aspen Plus, is used to predict the effect of various operating parameters including pressure, oxygen to coal, and steam to coal ratio on the product gas composition. The results obtained from the simulation were compared with experimental data in the literature. The predicted composition of the product gas was in general agreement with the established results. Carbon conversion increased with increasing oxygen-coal ratio and decreased with increasing steam-coal ratio. Steam to coal ratio and oxygen to coal ratios impacted produced syngas composition, while pressure did not have a large impact on the product syngas composition. A nonslagging moving bed gasifier would have to be limited to an oxygen-coal ratio of 0.26 to operate below the ash softening temperature. Slagging moving bed gasifiers, not limited by operating temperature, could achieve carbon conversion efficiency of 99.5% at oxygen-coal ratio of 0.33. The model is useful for predicting performance of the Usibelli coal in a moving bed gasifier using different operating parameters.